Exploring the Concept of Quality in Hospital Services from the Viewpoint of Patients and Companions: A Qualitative Study - Rohollah Kalhor; Samaneh Zolghadr; Marjan Darba; Atefeh Aghababaei (Shahid Sadoughi University of Medical Sciences, 2018)
Background: Quality is one of the factors affecting the success of service organizations. The quality of health services is from the patients' perspectives to the best service available in a timely, safe and economical manner. The aim of this article is to explain the concept of hospital services quality from patients and companions perspectives. Methods: The study was conducted using qualitative approach. The data were collected through semi-structured interviews Sampling was done purposefully and research interviews were ended once data saturation was achieved. Fifteen patients and thirteen companions were recruited. Findings were analyzed using Framework Analysis method. Results: The analysis of question about the concept of subjective quality of existence and the ideal quality led to emergence of themes including "emotional and psychological relations" and "customer-oriented" and "environmental and tangible factors”. Also, the themes for suggestion of quality improvement included "holding training classes", "improving facilities and amenities of health" and "improving human resource management." Conclusion: The findings showed that patients in addition to the physical problems of treatment location are concerned to human relations and even clinical treatment issues. In their opinion the relationships between patients and the medical staff, support and respect for the dignity, attention and importance of the personnel to patients and their personnel and environmental factors have a significant impact on the treatment process and the quality is satisfactory.